Some Relevant Aspects of Mining Taxes in Peru. Interview with Dr. Fernando Zuzunaga del Pino - Alva Cruz, Josselyn Estefanía (2014)
This interview aims to expose some relevant aspects of the mining taxes in our country. First, the discussion goes around the typical contracts of mining concessions and their relation with mining royalty and income tax, to then analyze the regulation of and anticipated recovery that looks to be an incentive for mining activity.Finally, the role of the right of effectiveness fee and mining royalty of mining concessions are analyzed, so are the consequences of this two in the mining sector.